The Impact of Managerial Ownership, Profitability, and Firm Size on Corporate Hedging Practices - Dwi Urip Wardoyo; Tiara Wardani; Irsa P. Rahmadani; Arifika S. Hartanti; Sri W. Sari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
In the current era of globalization, advances in technology and information encourage countries to expand market coverage by conducting transactions between countries. Companies in their activities to carry out international trade transactions, will face several risks caused by payments in foreign currencies. To minimize the possibility of these risks, companies can carry out hedging. The purpose of this study was to determine the effect of managerial ownership, profitability, and firm size on hedging decisions, either simultaneously or partially. The method used in this research is qualitative method with literature review of 19 related papers. The results show that managerial ownership, profitability, and firm size has a positive effect on company's hedging decision making.